Perbedaan Tingkat Kebugaran Jasmani Mahasiswa Prodi Teknik Kimia UPN “Veteran” Yogyakarta Kuliah Olahraga II Cabang Senam dan Bola Voli - Sumintarsih Sumintarsih; Hanafi Mustofa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine: 1) The effect of gymnastics on the level of physical fitness of students of the Chemical Engineering Study Program UPN "Veteran" Yogyakarta. 2) The influence of volleyball on the level of physical fitness of the Chemical Engineering Study Program students of UPN "Veteran" Yogyakarta. 3). Differences in the influence of gymnastics and volleyball on the level of physical fitness of students of the Chemical Engineering Study Program UPN "Veteran" Yogyakarta. This study uses an experimental method. The population in this study were students of the Chemical Engineering Study Program UPN "Veteran" Yogyakarta who took Sports II courses in the Gymnastics branch and volleyball branch. The sampling technique is purposive random sampling, the size of the sample taken for each group is 25 students. The data analysis technique in this study used the T test. The prerequisite test of data analysis used the normality test (Kolmogrov Sumirnov with = 0.05) and the homogeneity test of variance (Levene's Test, with = 0.05). The results of the study are as follows: 1) there is an effect of the gymnastics branch on increasing physical fitness of students of the Chemical Engineering Study Program UPN "Veteran" Yogyakarta, as evidenced by the average results of the pretest 27,160 and the posttest results of 29,120 with an average increase of 1.96 this means that there is an increase in physical fitness through gymnastics 2) there is an effect of volleyball on increasing the physical fitness of students of the Chemical Engineering Study Program UPN "Veteran" Yogyakarta, as evidenced by the average pretest result of 34,748 and the posttest result of 37,869 with an average increase of 3,121 this means that there is an increase in physical fitness through volleyball. 3) there is a significant difference in the effect between gymnastics and volleyball, the significance is 0.036 and the tcount is -2.152 at a significance level of 5%.